Convergence of diffusion processes. II - Makhno, S. Ya.; Махно, С. Я. (Institute of Mathematics, NAS of Ukraine, 1992)
Sufficient conditions for weak convergence of solutions of stochastic equations in terms of convergence of coefficients are obtained.